2020
DOI: 10.1007/s10389-020-01204-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of stressful life events and associations with mental health and general subjective health in the general population

Abstract: Aim We aim to determine the frequency of stressful life events (SLEs) and investigate the association of single and aggregated SLEs with mental health and general subjective health, which has not been reported for an aging representative sample to date. Subjects and methods A total of 12,947 participants (35-74 years old) of the Gutenberg Health Study (GHS) in Germany were analyzed. SLEs were analyzed at the item and aggregated level with unweighted and weighted sum scores. Additionally, the survey included me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…An unexpected result of the regression analysis—which demands more research- was that higher education was associated with higher odds of stressful event occurrence. Tibubos et al (2020) also found that the sum of aggregated stressful life events between the 65 and 74 years increased with higher socioeconomic status. Nevertheless, the sum of events is not equivalent to the intensity of them.…”
Section: Discussionmentioning
confidence: 78%
“…An unexpected result of the regression analysis—which demands more research- was that higher education was associated with higher odds of stressful event occurrence. Tibubos et al (2020) also found that the sum of aggregated stressful life events between the 65 and 74 years increased with higher socioeconomic status. Nevertheless, the sum of events is not equivalent to the intensity of them.…”
Section: Discussionmentioning
confidence: 78%
“…Bereavement, including widowhood and loss of offspring, is consistently and strongly related to depression (28,(31)(32)(33). However, when facing widowhood, older women are less vulnerable than older men (34).…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
“…Stressful life events have a modest but significant relationship with depression, but whether this is a causal effect is unclear (20,32,37,39). There is a stronger association between stressful life events and depression when the event is more severe or there are more events (32,39).…”
Section: Stressful Life Events and Depressionmentioning
confidence: 99%
“…Since the concept of stress was introduced to the scientific community in 1936 by Hans Selye [ 58 , 59 ], a strong link between CPSS/CPPS and depression has been reported. Many studies and meta-analyses have demonstrated an elevated depression risk following childhood maltreatment and adverse life events in adolescence and adulthood [ 21 , 60 66 ]. The biological mechanisms that translate this form of environmental stress into the nosological entity called depression are not yet fully understood, but the immune system, in particular cytokines and microglia, is proposed to be a principal component [ 16 , 35 , 67 69 ].…”
Section: From Stress To Depression: the Emerging Role Of The Immune Systemmentioning
confidence: 99%